EFFICACY OF SOLIFENACIN FOR TREATMENT OF OVERACTIVE BLADDER IN WOMEN - JEHAN, S; REHMAN, SU; HAYAT, A; WAHAB, A; IZHAR, M (Biological and Clinical Sciences Research Journal, 2024)
Overactive bladder (OAB) significantly affects the quality of life in women due to symptoms such as urgency, increased frequency, and incontinence. Solifenacin, a muscarinic receptor antagonist, has been widely used to treat OAB, but its efficacy needs further validation in diverse populations. Objective: To determine solifenacin's efficacy for treating overactive bladder in women. Descriptive Case Series Department of Urology, Institute of Kidney, from 1st January 2023 to 30th June 2023.Methods: Seventy-seven female patients with overactive bladder diagnosed by consultant urologist on clinical presentation were included in this study. The WHO Sample Size calculator calculated the sample size with 92.20% efficacy of solifenacin, 80% power of the test, and 5% significance level. Clinical evaluation was done, and the baseline severity of symptoms was recorded. Baseline severity was defined according to the number of incontinence episodes/24 h, number of urgency episodes/24 h, and micturition frequency/24 h. Patients were advised of solifenacin 5 mg OD for twelve weeks. Patients were followed up in the twelfth week, and efficacy was determined regarding improvement in the severity of OAB symptoms, i.e., improvement of at least 03 points from the baseline. Results: As per the efficacy of Solifenacin in treating OAB symptoms, 37 (86.0%) showed effective results. Conclusion: Solifenacin showed significant effectiveness in terms of improvement in the severity of OAB symptoms in female patients.